A novel consortium of Lactobacillus rhamnosus and Streptococcus thermophilus for increased access to functional fermented foods. Issue 1 (December 2015) - Kort, Remco; Westerik, Nieke; Mariela Serrano, L.; Douillard, François; Gottstein, Willi; Mukisa, Ivan; Tuijn, Coosje; Basten, Lisa; Hafkamp, Bert; Meijer, Wilco; Teusink, Bas; Vos, Willem; et al.
Abstract Background The lactic acid bacteriumLactobacillus rhamnosus GG is the most studied probiotic bacterium with proven health benefits upon oral intake, including the alleviation of diarrhea. The mission of the Yoba for Life foundation is to provide impoverished communities in Africa increased access toLactobacillus rhamnosus GG under the nameLactobacillus rhamnosus yoba 2012, world's first generic probiotic strain. We have been able to overcome the strain's limitations to grow in food matrices like milk, by formulating a dried starter consortium withStreptococcus thermophilus that enables the propagation of both strains in milk and other food matrices. The affordable seed culture is used by people in resource-poor communities. Results We usedS. thermophilus C106 as an adjuvant culture for the propagation ofL. rhamnosus yoba 2012 in a variety of fermented foods up to concentrations, because of its endogenous proteolytic activity, ability to degrade lactose and other synergistic effects. Subsequently, L. rhamnosus could reach final titers of 1E+09 CFU ml−1, which is sufficient to comply with the recommended daily dose for probiotics. The specific metabolic interactions between the two strains were derived from the full genome sequences ofL. rhamnosus GG andS. thermophilus C106. The piliation of theL. rhamnosus yoba 2012, required for epithelial adhesion and inflammatory signaling in the human host, was stable during growth in milk for two rounds of fermentation. Sachets prepared with the two strains, yoba 2012 and C106, retained viability for at least 2 years. Conclusions A stable dried seed culture has been developed which facilitates local and low-cost production of a wide range of fermented foods that subsequently act as delivery vehicles for beneficial bacteria to communities in east Africa.